THE CORRECT AND EFFECTIVE WAY TO TREAT PSORIASIS - G’ofurjonova Irodaxon Qobiljon qizi; Foziljonova Nodira; Ahatova Guldona; Marasulova Madinabonu Arabboy qizi (Galaxy International Interdisciplinary Research Journal, 2022)
This article describes in detail the correct and effective treatment of non-infectious chronic psoriasis, the etiology of which is still unknown, despite in-depth medical research. Is psoriasis contagious through this article? Is there a cure for psoriasis? You can find answers to the following questions: